THE GOSPEL CODE IN THE “ITALIAN” POEMS BY V.F. KHODASEVICH (Philological Studies, 2020)
The article explores the images and the plots of the Gospel in V.F. Khodasevich’s “Italian” poems. In his pre-emigration poetry, we find the plot of the Flight into Egypt. Another poem written in emigration, actualizes the events of Holy Week. Intermedia is the characteristic of the Gospel images and plots in Khodasevich’s poetry. The key image in these poems is the image of the Virgin Mary, which is comparable to the female images and the image of Jesus Christ in the works of A.A. Block. The author of the article comes to the conclusion that the space of Italy in Khodasevich’s poetry is equated with the Gospel space. In the pre-emigration poem, Italy is depicted in an enlightened religious atmosphere. In the poem written in emigration, Khodasevich views the events of Holy Week through the prism of the Russian revolution of 1917.
Keywords: V.F. Khodasevich; A.A. Blok; Virgin Mary; Flight into Egypt; Holy week; Italy; emigration